Analysis of the Influence of Religiosity Values In Reducing Consumptive Behavior in Indonesian Muslim Consumers - Mujahidin; Zainuddin; Rahmadani, Nahdah; Rusmana Putri, Qisty Amalina (UPT Publikasi Ilmiah UNISBA, 2024)
This research aims to analyze the influence of religiosity values on consumer behavior among Muslim consumers in Palopo City. Using a quantitative approach and survey methods, data was collected through questionnaires distributed to a sample of Muslim consumers in Palopo City. Linear regression analysis is used to test the relationship between religiosity variables and consumer behavior. The research results show that there is a significant influence of religiosity values in reducing consumptive behavior among Muslim consumers in Palopo City. The implications of this research provide a deeper understanding of how religiosity values can influence consumer behavior, as well as providing useful insights for marketers and business practitioners in developing marketing strategies that are in accordance with the religious values of Muslim consumers